2014
DOI: 10.1080/00222933.2013.840941
|View full text |Cite
|
Sign up to set email alerts
|

The muscles, body wall and valve-opening mechanism of extant craniid (inarticulated) brachiopods

Abstract: Specimens of six species of craniid brachiopod were dissected and the musculature, body wall and mantle were examined. New names are proposed for the "brachial protractor" and "brachial retractor" muscles. The "brachial elevator" muscles are part of the anterior adductor muscles, a small bundle of translucent quick-muscle partially enclosed by a larger, curving bundle of the dark-coloured slow-muscle. A new ring muscle is described. The lophophore arms are extended and retracted by the hydrostatic skeleton and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 14 publications
4
40
2
Order By: Relevance
“…(). Recent craniiforms lack articulation and open their shells hydraulically with the assistance of the outside lateral muscles attached anteriorly to the body wall (Robinson ). This shell‐opening mechanism differs markedly from that found in the lingulates, which have well developed dermal muscles (Hyman ; Popov et al .…”
Section: Early Palaeozoic Radiation Of the Brachiopodamentioning
confidence: 97%
“…(). Recent craniiforms lack articulation and open their shells hydraulically with the assistance of the outside lateral muscles attached anteriorly to the body wall (Robinson ). This shell‐opening mechanism differs markedly from that found in the lingulates, which have well developed dermal muscles (Hyman ; Popov et al .…”
Section: Early Palaeozoic Radiation Of the Brachiopodamentioning
confidence: 97%
“…Robinson and Lee (2007, p. 129) suggested that 'by having the brachial protractor muscles attachment point situated more ventrally, on the processes, V. quenstedti may be able to manipulate its lophophore more effectively as the muscles are not all contracting dorsally'. Robinson (2014) found that the so-called brachial protractor muscles do not attach to the lophophore and renamed them the small anterior muscles. The function of these very small muscles, and how this function is (presumably) enhanced by the development of the processes they attach to in Valdiviathyris, remains unknown.…”
Section: Remarksmentioning
confidence: 99%
“…New terminology for some craniid muscles, based on dissections of specimens of six extant species, was introduced by the author (Robinson 2014). New terms include small anterior muscles (previously known as the brachial protractor muscles, Blochmann [1892]) and support structure (previously known as the brachial retractor muscles).…”
Section: New Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…82°47'O -- 8 Octobre 1898 -Profondeur : 500 m environ." Depth range: 40 --3310 m. References: Brand et al (2003), Cohen et al (2014), Cooper (1973a, Dall (1921), Eichler (1911), Foster (1969Foster ( , 1974, Hatai (1965), Robinson (2014), Sáiz et al (2008), Thomson (1918), Zezina ( , 1981Zezina ( , 1994Zezina ( , 1998, Zezina & Pakhnevich (1998).…”
Section: Carnets Géol Cg2017_b03 16mentioning
confidence: 99%